ATTITUDE TOWARDS E-LEARNING AMONG PROSPECTIVE TEACHERS IN AIZAWL CITY (International Journal of Food and Nutritional Sciences, 2022)
The present study was conducted to measure the attitude towards e-learning among prospective teachers in Aizawl City, and to compare their attitude towards it with reference to their age and their gender. Census survey method was adopted in which 728 samples were collected. Attitude Towards e-learning Scale developed by Dimpal Rani was used for collecting data. The result has revealed that prospective teachers have average attitude towards e-learning and their attitude scores did not differ significantly with respect to their age or gender